Exploring the Concept of Peace in Islamic Teachings: A Comprehensive Analysis of Surah Al-Anfal Ayat 61 - Nasywa Hilmi (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
This research explores the conceptualization of peace in Islamic teachings, focusing on Surah Al-Anfal Verse 61 in the Quran. The method employed in this study is a literature review. The data collected and analyzed are secondary research findings from books, journals, articles, websites, and other relevant sources. Furthermore, the data analysis technique used in this research involves content analysis. The research findings reveal a comprehensive discussion of the relationship between Islam and the principles of peace. Verses in the Quran, particularly Surah Al-Anfal Verse 61, guide believers to lean towards peace and trust Allah when faced with the desire for peace. The Quran portrays Islam as a religion of peace, where peace is the general rule, and war is only justified in specific, compelling circumstances. The fundamental goal of Islam is to transform human thinking, initiating an intellectual revolution based on the oneness of God or Tawhid. The implications of this research extend beyond the academic realm, influencing broader discourse on Islam and peace. The proactive roles of Islamic organizations such as NU and Muhammadiyah in regional and international peace initiatives demonstrate the practical application of Islamic values. This research provides recommendations for universities to actively promote peace in contemporary society by emphasizing the crucial values of peace and security in human existence, as outlined in Surah Al-Anfal Verse 61.